Are Behavior Rating Scales Able to Identify Behavioral Changes in Preschool Children Undergoing a Dental Intervention? A Systematic Review - Jéssica Aparecida da Silva; Saul Martins Paiva; Daniele Masterson Tavares Pereira; Lucianne Cople Maia; Laura Guimarães Primo; Andréa Fonseca-Gonçalves (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the scientific evidence concerning the behavior rating scales efficiency to identify behavioral changes in preschool children undergoing dental treatment, through a systematic review. Material and Methods: MEDLINE/PubMed, Scopus, Cochrane Library, Web of Science, BVS databases and grey literature were searched. Also, a hand search of the included studies reference lists was conducted. Studies that evaluated healthy preschoolers' behavior before and after invasive dental treatments to observe behavioral changes were included. Two independent reviewers selected studies, extracted data and analyzed the risk of bias with a tool for before-and-after studies. The certainty of the evidence was evaluated with the GRADE approach. Results: Three studies were included. The Frankl Scale and North Carolina Behavior Scale were used in these studies. Both scales were able to identify behavioral changes in preschool children undergoing a dental intervention, although two of these included studies were considered fair with a high risk of bias, and one considered good with a low risk of bias. Conclusion: Although Frankl and North Carolina behavior scales were able to identify changes in the children`s behavior during dental treatment, these findings are not supported by strong evidence. Thus, further well-designed studies are needed to confirm this evidence.